Statistical study on engine knock oscillation and heat release using multiple spark plugs and pressure sensors. (1st August 2021) - Shi, Hao; Uddeen, Kalim; An, Yanzhao; Pei, Yiqiang; Johansson, Bengt
Highlights: Multiple spark plugs were used to trigger controllable knock. Multiple pressure sensors were used to monitor the knock vibrating signals. A mathematical model was developed to predict the knock strength. The knock heat release fraction was calculated and related with knock intensity. The wave propagation during knock was analyzed by extracting the primary resonance mode. Abstract: Engine knock has been an inherent problem that limits engine efficiency improvement and threatens engine service life. To trigger the controllable knock, a specialized liner with installing four side spark plugs mounted on the cylinder head are used in this study to produce various in-cylinder flame propagation. Various spark strategies (e.g., spark timing, spark number, spark location) are applied to generate different auto-ignition sites and knock characteristics. Up to five channels of pressure signal are collected to analyze the knock intensities regarding different spark strategies. To investigate the knock-induced fluctuations and heat release, we use the multiple correlations to evaluate the maximum amplitude of pressure oscillation (MAPO) respecting different influential factors and building a multiple linear regression (MLR) model for MAPO prediction and validate it against the experiment results. Besides, the Wiebe function and curve-fitting techniques are applied to estimate the energy released by auto-ignition in each cycle, and its relations with knock intensity are assessed. The results show that the average growth of pre-oscillation plays an important role in MAPO value (correlation coefficient, r_s = 0.965), the established MLR model possesses high accuracy for MAPO prediction. The pressure oscillation regarding the 1st resonance mode is extracted from the band-pass filtered signal, representing the main pressure oscillating process. Compared with the single spark ignition, triggering more spark plugs could boost the fuel consumption rate, while shortening the knocking combustion duration and reducing the heat release fraction contributed by auto-ignition. At the same CA50 (9 CAD aTDC), the four spark ignition leads to the least heat release fluctuations than other spark strategies. With advancing the CA50, the heat release fraction produced by knock increases at first then reduces due to the thermodynamic conditions and the flame propagation. Activating two or three spark plugs, the rising rate of the heat release rate goes up, but the knock-induced heat release fraction decreases. Moreover, the primary acoustic resonance mode (1, 0) gives more regular knock vibrations than the mixing form (including mode (1, 0), (0, 1), (2, 0), etc.), the average traveling distance of acoustic wave in the time gap of receiving two continuous signals is very close to the cylinder bore. The results give insights into the pressure wave propagation during knock and the relations between knock conditions, pressure oscillations, and heat release.